Global Pandemic Conditions and List of Possible Medications and Vaccines for the Treatment of COVID-19: A Review - Mohammad Mukim; Atul Kabra; Siwani Devi; Mohit Chaturvedi; Rakesh Patel (Borneo Journal of Pharmacy, 2020)
At the end of December 2019, a novel coronavirus was identified which caused severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) with a disease known as coronavirus disease 2019 (COVID-19). The virus first originated in the city of Wuhan in China, causing symptoms such as pneumonic plague, which began in the Wuhan and then spread throughout the world with high transmission efficiency. Special precautions and care are needed such as leaving the public area, covering your mouth with a mask, not shaking hands, washing hands, and sanitation from time to time. Infection due to SARS-CoV-2 shows several symptoms, one of which is very often the patient shows difficulty breathing. Currently, COVID-19 has been declared a global pandemic and has almost attacked all countries in the world, including in India which has one of the largest human populations in the entire world. One of the challenges in handling COVID-19 is the unavailability of drugs or special vaccines to treat the disease, so clinical practitioners and academics are currently testing various drugs to see how they affect the COVID-19 patients. Some of the drugs tested provide effective mechanisms against SARS-CoV-2, such as chloroquine, remdesivir, lopinavir, and vaccines under development. These drugs are still being tested and are now at the forefront to combat the effects of SARS-CoV-2 infection. This review article will discuss all kinds of ins and outs of SARS-CoV-2 and COVID-19, including the transmission method, how to prevent it, as well as various drugs and vaccines currently used in handling COVID-19.